How Does AI Improve Clinical Trial Design? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Clinical trials are the cornerstone of medical advancement, but they are often a lengthy, expensive, and complex process. From recruiting patients to collect...
Keywords: Drug Discovery and Pharmaceutical AI; Improve; Clinical; Trial; Artificial Intelligence; Healthcare